Human Resource Management Factors in Financial Analysis of Securities Companies - Thi Mo, Nguyen; Minh Tien, Cao; Lan Anh, Tran Thi; Van Hai, Tran (International Journal of Economics and Financial Issues, 2024)
The outcomes of financial analysis serve as the basis for crucial decision-making in business operations. However, many small-scale securities companies tend to overlook this aspect. This study aims to investigate the relationship between financial analysis activities and business outcomes of small-scale securities companies in Vietnam. Data were collected from 92 respondents working in 27 small-scale securities companies (with owner equity of less than 250 billion Vietnamese Dong), holding positions such as management (directors, assistant directors, financial directors, chief accountants) and staff (financial and accounting personnel) involved in financial and accounting operations of Vietnamese securities companies. Sampling was conducted selectively from September 2023 to December 2023. Utilizing quantitative research, the Partial Least Squares Structural Equation Modeling (PLS-SEM) method was employed using SPSS 20 and AMOS 20 software. Results indicate that Financial Analysis Method (MAF) and Financial Analysis Content (variable FAC) positively influence financial analysis activities of small securities companies. Recommendations to enhance securities companies’ business outcomes include (i) employing the EVA technique in financial analysis, (ii) improving management capabilities in financial report analysis, (iii) enhancing the skills of accounting and financial staff, and (iv) applying and operating professional ethical principles.